Assessing Local Community's Perception Towards the Development of Smart City in Small Island Developing States (SIDS): Evidence from Mauritius - Sannegadu, Rajesh; Juwaheer, Thanika Devi; Pudaruth, Sharmila; Gunesh, Raj; Vencataya, Lomendra (2022)
Purpose: As local communities are embedded into the development of smart cities, their perceptions and attitudes towards these projects are crucial to ensure sustainable socio-economic development. This paper aims at assessing local community’s perception towards the development of smart city in Mauritius.